1987
DOI: 10.1007/bf00343701
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 ? and ? genes: linkage on chromosome 2 in the mouse

Abstract: Two interleukin-1 polypeptides, alpha and beta, are known, and cDNAs corresponding to each have been described. Genomic cloning and Southern blotting experiments suggest that in the mouse each is encoded by a gene present in one copy per haploid genome. Analysis of a panel of somatic cell hybrids carrying various mouse chromosomes on a constant Chinese hamster background indicates that both genes map to mouse chromosome 2. Further, analysis of the inheritance of DNA restriction fragment length polymorphisms as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

1988
1988
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…(i) Prn-p. Three Prn-p cDNA probes were used. Both a 2-kilobase (kb) insert from a hamster PrP cDNA clone (44) and a 900-base-pair (bp) EcoRI fragment from subclone 13 of a mouse cDNA (11) (20) and the Klenow fragment of DNA polymerase I (61).…”
Section: Methodsmentioning
confidence: 99%
“…(i) Prn-p. Three Prn-p cDNA probes were used. Both a 2-kilobase (kb) insert from a hamster PrP cDNA clone (44) and a 900-base-pair (bp) EcoRI fragment from subclone 13 of a mouse cDNA (11) (20) and the Klenow fragment of DNA polymerase I (61).…”
Section: Methodsmentioning
confidence: 99%
“…There are two proIL-1 genes (proIL-lco and proIL-113) coding for distinct proteins which are observed in many different species (7,18). The two proIL-1 genes are located on human chromosome 2 (11,30,48) and show a high conservation of exon/intron structure (7). IL-1 has a variety of biological activities on a wide range of tissues (see reference 13 for a review).…”
mentioning
confidence: 99%
“…A DNA probe, corresponding to a 0.2-kb restriction fragment unique to the region 3' to the breakpoint on the mutant 7.5-kb fragment (Fig. 3B), was hybridized to DNA from somatic cell hybrids containing, along with other mouse chromosomes, either both chromosomes 2 and 17 (hybrid line BEM 1-4) or just mouse chromosome 17 (hybrid line R44-1) (23). Results showed that the probes hybridized to chromosome 2 but not to chromosome 17 (data not shown).…”
mentioning
confidence: 99%